Urbanization and human security in post-colonial Africa - Eyita-Okon, Ekeminiabasi (Frontiers in Sustainable Cities, 2022)
Urbanization has been unprecedented in post-colonial Africa. While cities and towns (urban areas) are crucial to bolstering economic activities, they are equally perceived as the scene for social and economic problems. This in turn exacerbates urban human insecurity. The paper draws on qualitative research method in exploring the challenges and opportunities that undermine or facilitate achieving sustainable and inclusive cities in post-colonial Africa. Particularly, the role of the African Union through Agenda 2063 in materializing sustainable and efficient cities, against the backdrop of climate change, in post-colonial Africa. The study present statistics on urbanization and human security trends in the region such as the rate of urbanization, quality of life in informal settlements and slums, the share of urban population living in slums, and a correlation matrix on the quality of human development in slums. The study finds that while varied strides have been taken across the African continent on a national level, the problem of coordination, structural/systemic violence, prevalence of external vision for Africa's development, and gaps in policy implementation pose a threat to adequately addressing the perils of urbanization on human security in post-colonial Africa. Irrespective, Agenda 2063 offers the continent the opportunity to prioritize urban human insecurity issues as an emerging non-conventional security threat requiring securitization. Also, it offers an opportunity to re-center people at the heart of policy decisions while creating incentives for member states to meet the aspirations, goals, and targets set out in Agenda 2063, as it pertains to sustainable and inclusive cities in post-colonial Africa.